Convergent validity of the interRAI-HC for societal costs estimates in comparison with the RUD Lite instrument in community dwelling older adults. Issue 1 (December 2016) - van Lier, Lisanne; van der Roest, Henriëtte; van Hout, Hein; van Eenoo, Liza; Declercq, Anja; Garms-Homolová, Vjenka; Onder, Graziano; Finne-Soveri, Harriet; Jónsson, Pálmi; Hertogh, Cees; Bosmans, Judith.
Abstract Background The interRAI-Home Care (interRAI-HC) instrument is commonly used in routine care to assess care and service needs, resource utilisation and health outcomes of community dwelling home care clients. Potentially, the interRAI-HC can also be used to calculate societal costs in economic evaluations. The purpose of this study was to assess the convergent validity of the interRAI-HC instrument in comparison with the RUD Lite instrument for the calculation of societal costs among care-dependent community dwelling older adults. Methods A within-subject design was used. Participants were 65 years and older and received professional community care in five countries. The RUD Lite was administered by trained (research) nurses or self-reports within 4 weeks after the interRAI-HC assessment. Agreement between the interRAI-HC and RUD Lite estimates was assessed using Spearman's correlation coefficients. We hypothesised that there was strong correlation (Spearman'sρ > 0.5) between resource utilisation estimates, costs of care estimates and total societal cost estimates derived from both instruments. Results Strong correlation was found between RUD Lite and interRAI-HC resource utilisation assessments for eight out of ten resource utilisation items. Total societal costs according to the RUD Lite were statistically significantly lower than according to the interRAI-HC (mean difference €-804, 95 % CI −1340; −269). The correlation between the instruments for total societal costs and all six cost categories was strong. Conclusions The interRAI-HC has good convergent validity as compared with the RUD-Lite instrument to estimate societal cost of resource utilisation in community dwelling older adults. Since interRAI-HC assessments are part of routine care in many community care organisations and countries already, this finding may increase the feasibility of performing economic evaluations among community dwelling older adults.